PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD DALAM MENINGKATKAN PEMAHAMAN MATEMATIS SISWA PADA POKOK BAHASAN BANGUN RUANG - Nida Jarmita (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2012)
Quasi-experimental study design with the pre-test and post-test is aimed to obtain objectiveinformation about the effectiveness of cooperative learning type STAD in improving students' mathematical understanding of class V MIN. The population of this study is student of class VMIN in the city of Banda Aceh. Based on the results of data analysis, improving the ability ofmathematical understanding in the experimental class and control class is quietly different in terms of level of school (good, adequate and low). The difference increased capability is then tested statistically by ANOVA test using two pathways with significance level (Î±) = 0,05. From the results of different test can be concluded that the increased understanding ofmathematical abilities of students through cooperative learning type STAD better than on improving the understanding of mathematical abilities of students through conventional learning.